2014
DOI: 10.1159/000368932
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of AMP-Activated Protein Kinase Agonists in Kidney Ischemia-Reperfusion: Autophagy and Cellular Stress Markers

Abstract: Background: Kidney ischemia-reperfusion is a form of acute kidney injury resulting in a cascade of cellular events prompting rapid cellular damage and suppression of kidney function. A cellular response to ischemic stress is the activation of AMP-activated protein kinase (AMPK), where AMPK induces a number of homeostatic and renoprotective mechanisms, including autophagy. However, whether autophagy is beneficial or detrimental in ischemia-reperfusion remains controversial. We investigated the effects of agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 75 publications
7
35
0
Order By: Relevance
“…As AMPK has been suggested to be implicated in the renoprotective effects of metformin34, we next tested the potential role of AMPK in the 3dUUO model of renal damage using AMPK-β1 −/− mice. The AMPK-β1 −/− model was used for these experiments because KO mouse was found to practically ablate the expression of AMPK active enzyme in mouse kidney35.…”
Section: Resultsmentioning
confidence: 99%
“…As AMPK has been suggested to be implicated in the renoprotective effects of metformin34, we next tested the potential role of AMPK in the 3dUUO model of renal damage using AMPK-β1 −/− mice. The AMPK-β1 −/− model was used for these experiments because KO mouse was found to practically ablate the expression of AMPK active enzyme in mouse kidney35.…”
Section: Resultsmentioning
confidence: 99%
“…It had been reported that AMPK and autophagy were activated in renal cells under stress conditions, which can cause programmed cell death (44). On the other hand, supraphysiologically activating AMPK by AICAR and metformin was reported to exert a beneficial effect in kidney ischemia-reperfusion (45). Although the underlying mechanism for why AMPK␥2 RG , but not AMPK␥2 NI , mice showed kidney injury is not fully understood, we speculate that the kidney injury might be associated with the higher baseline activity of AMPK␥2 RG and the "loss of AMP response" of AMPK␥2 RG , in which cellular AMP cannot bind to one of the binding domains in AMPK ␥-subunit (3).…”
Section: Discussionmentioning
confidence: 99%
“…Although overexpression of both BNIP3 and sestrin 2 induced autophagy as measured by LC3-II formation, only BNIP3 selectively induced mitophagy as visualized by confocal and electron microscopy 72 . The expression of PINK, a marker of mitophagy, was increased during renal ischemia-reperfusion injury 73 . Another study has shown that mitophagy in the kidneys of a rat fed low-calorie diet was markedly increased and ameliorated oxidative damage compared to that of high-calorie fed rats 74 .…”
Section: Introductionmentioning
confidence: 99%